Prevalence and risk of progressive aortic aneurysm and dissection in adults with conotruncal anomalies. (22nd December 2021) - Egbe, Alexander C; Miranda, William R; Bonnichsen, Crystal R; Jain, C Charles; Crestanello, Juan A; Francois, Christopher; Katta, Renuka R; Iftikhar, Momina; Goda, Ahmed Y; Andi, Kartik; Gandhi, Sangeetha; Connolly, Heidi M
Abstract: Aims: Conotruncal anomalies share common embryogenic defects of the outflow tracts and great arteries, which result in a predisposition to aortic aneurysms. The purpose of this study was to describe the prevalence and risk of progressive aortic aneurysms in adults with conotruncal anomalies. Methods and results: Retrospective study of adults with conotruncal anomalies that underwent cross-sectional imaging 2003–20. Aneurysm was defined as aortic root/mid-ascending aorta >2.1 mm/m 2 />1.9 mm/m 2, progressive aneurysm as increase by >2 mm, and severe aneurysm as dimension >50 mm. Of 2261 patients (38 ± 12 years; male 58%), 1167 (52%) had an aortic aneurysm, and 205 (14%) had a severe aortic aneurysm. Mean annual increase in aortic root/mid-ascending aorta was 0.3 ± 0.1 mm/0.2 ± 0.1 mm. The 3-, 5-, and 7-year cumulative incidence of the progressive aortic aneurysm was 4%, 7%, and 9%, respectively. The rate of aneurysm growth decreased with age, with no significant growth after age 40 years. There was an excellent correlation between aortic indices from cross-sectional imaging and echocardiography. Of 950 females, 184 had ≥1 pregnancy, and 81 (44%) of the 184 patients had aortic aneurysm prior to pregnancy. There was no aortic dissection or progression of the aortic aneurysm during pregnancy. Overall, there was no aortic dissection during 7984 patient-years of follow-up. Conclusions: Aortic aneurysm was common in patients with conotruncal anomalies. However, the risk of progressive aneurysm or dissection was low. Collectively, these data suggest a benign natural history and perhaps a less frequent need for cross-sectional imaging. Further studies are required to determine the optimal timing for surgical intervention in this population. Graphical Abstract: